The effects of using magery to elicit an external focus of attention - Yamada, M.; Raisbeck, L. D.; Porter, J. M. (Research Quarterly for Exercise and Sport, 2021)
Background: An external focus of attention has been shown to be superior to adopting an internal focus of attention in a variety of motor skills. Purpose: To examine the efficacy of directing attention externally toward an imagined object when performing the standing long jump. This form of practice was compared to a group of participants that practiced the same motor skill while directing their attention toward an object that was physically present in the practice environment. Method: All participants performed a series of standing long-jumps on a rubber mat. Participants were randomly assigned to either an external focus condition where they were instructed to jump as close as possible to a cone that was directly in front of them. Or they were assigned to an imagery condition in which they were instructed to jump toward an imagined cone. Following acquisition trials, a 24-hr retention and transfer test was completed by all participants. Results: Significant improvement was demonstrated by both groups during acquisition, retention and transfer phases compared to the baseline measure. However, no significant differences were observed between the two experimental conditions. Conclusion: The findings of this experiment demonstrate that attention directed externally toward a physical object and an imagined object has a similar effect.